[Rezension von: Hildebrandt, Samuel, Vast as the sea : Hebrew poetry and the human condition] - Firth, David G. (European journal of theology, 2025)
Hildebrandt’s study explores the interface between human experience and its expression in the Old Testament. An introduction and epilogue outline the key issues explored, while six chapters provide a close reading of particular poems and explore the significance of each one for a specific aspect of the human experience. A beautifully written work, it serves as a theological reflection that takes seriously both the text of these poems and the challenges and joys of the human condition.